DNA based analyses of microbiota in fat fraction of raw milk - Blänning, Caroline (SLU/Department of Molecular Sciences, 2017)
The microbiota of raw milk is complex and the analysis methods have during the years developed from culturing to molecular based methods, allowing more precise descriptions of the composition. This project included both cultivation and molecular methods to compile the distri-bution of microorganisms in the whole milk, since the most common way to day to investigate milk microbiota is based on defatted milk. The goal was to explore how big part of the microbiota that is connect-ed to the milk fat fraction and if the already existing method for DNA based analyses of milk microbiota is suitable also for detection of mi-crobiota in whole milk. In this project, raw milk samples were spiked with Lactobacillus reuteri DSM, Lactobacillus reuteri PTA, Escherichia coli and Staphylococcus aureus. The samples were centrifuged and the fractions (pellet, supernatant and fat) were cultured to identify the bac-terial distribution. The molecular method consisted of DNA extractions, Terminal Restriction Fragment Length Polymorphism (T-RFLP) and quantitative PCR (qPCR) also based on whole milk, spiked with the same bacteria as during the cultivation part. PowerFood Microbial DNA Isolation kit (MoBio Laboratories Inc.) was used for four different ex-traction methods. For comparing the DNA extraction methods and bac-terial community, the T-RFLP was used. Additionally, qPCR was per-formed for total and specific targeting of bacteria and quantification. The results from the cultivation part showed that the highest amounts of colony forming units (CFU) originated from the fat fraction. The mo-lecular methods confirmed the pattern as the T-RFLP analyses from the whole milk samples showed more traces of bacteria. The qPCR showed that the whole milk samples contained more DNA than the skim milk samples. In conclusion, the PowerFood kit without additions of solvents can be used for DNA preparation followed by PCR and/or T-RFLP/sequencing when analyzing the microbiota in whole milk.